[March leaders walking on University Drive?] (1995)
Three Black march participants are walking on University Drive, in front of the Dexter building. They are probably (based on related photographs in this collection) leading a march. There is a work truck with a California license plate to the left of the group, and the truck has tools in its bed. There is fencing near the truck. A student wearing a backpack is walking in the opposite direction of the group. An awning attached to Dexter Building reads 'The Cellar'.